Consumer Behavior Intentions to Purchase Daily Needs through Online Store Channel - Moh. Wahyudin; Henry Yuliando; Amalia Savitri (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
The inception of the 4.0 industrial era led to the evolution of internet information technology, which significantly changed the business sector’s marketing, transaction, and payment systems into online stores. This new marketplace is an important business infrastructure used to develop marketing strategies in this technological era. Therefore, it enables companies or enterprises, including those in the retail sector, to remotely sell daily products, such as cooking needs, foods, snacks, beverages, toiletries, and laundries through various online platforms. Furthermore, these companies need to creatively and anticipatively participate in the various trading competition by having an online shopping channel. This study aims to measure consumer behavior intention in using the online store channel to purchase daily needs products in order to determine the influence of convenience and risk transactions on behavioral intentions. Data were obtained from respondents that consistently make use of online stores channel. The result showed that consumers’ ease and convenience during transactions, especially in terms of payment and delivery service, have a positive and significant effect on their attitude and behavioral intention to use online store channel to purchase daily needs products.